LA INACTIVIDAD ADMINISTRATIVA EN LA ADMINISTRACIÓN PÚBLICA - Rodríguez Lozano, Luis Gerardo (2019)
The object of study of this article is the administrative inactivity in the sphere of publicadministration, when it is expressed by two legal figures of administrative silence:negative silence and positive silence, both represent a violation of the duties of action established by the procedural rule of the public administration. Unfortunately, this problematichas not been addressed in a systematic and methodological manner, whichmakes it impossible to clearly establish a conceptual and theoretical framework thatcould explain and propose solutions to the problem of administrative inactivity. Theobligation to resolve is a specific duty of the Administration to resolve the requests thatarise in the administrative procedures, as well to notify the resolution resulting from theprocedure, but the violation of the constitutional norm is not a cause of administrativeinactivity, so isn’t admissible to equate the administrative silence with the right of petition,since what article 8 protects is the duty to respond but that doesn’t mean that thedamaged caused by the omission is repaired. The negative silence is characterized by theeffect that is given to the refusal to respond the requests, and at the same time rejectsthe request of the petitioner. The positive silence consists in a presumptive act, the lawmakersought to establish equivalence with respect the administrative act that would becomparable to the affirmative authorization that substitutes, but the act lacking of legitimacyproduce legal uncertainty for the administrated.